Influence of the Rigid Connection Between Discs in the Tetrahedral Prisms on Equivalent Stresses When Cutting Work Faces - Khoreshok A. A. Aleksey Alekseevich; Mametyev L. E.; Borisov A. Yu.; Vorobyev A. V. Aleksey Vasilievich (2016, 2016)
Title screen